Insights into microorganisms, associated factors, and the oral microbiome in infective endocarditis patients - Ismail, Ayden; Yogarajah, Amieth; Falconer, Joseph Luke; Dworakowski, Rafal; Watson, Samuel; Breeze, Jonathan; Gunning, Margaret; Khan, Habib; Hussain, Azhar; Howard, James P.; Cheong, Phoebe; Shah, Mira; et al. (Frontiers in Oral Health, 2024)
Introduction Infective Endocarditis (IE) is a rare, life-threatening infection of the endocardium with multisystem effects. Culprit microorganisms derived from different niches circulate through the bloodstream and attach to the endocardium, particularly the heart valves. This study aimed to investigate culprit microorganisms among a cross-sectional cohort of IE patients, their associated factors, and to explore the potential relationship to the oral microbiome. Methods In this observational study, we undertook a cross-sectional analysis of 392 medical records from patients diagnosed with IE. The primary outcome of this study was to analyse the association between the IE culprit microorganisms and the underlying anatomical types of IE (native valve (NVE), prosthetic valve (PVE), or cardiac device-related (CDE)). Secondary outcomes encompassed a comparative analysis of additional factors, including: the treatment approaches for IE, and the categorisation of blood cultures, extending to both genus and species levels. Additionally, we cross-referenced and compared the species-level identification of IE bacteraemia outcome measures with data from the expanded Human Oral Microbiome Database (eHOMD). Results A culprit microorganism was identified in 299 (76.28%) case participants. Staphylococcal infections were the most common (p < 0.001), responsible for 130 (33.16%) hospitalisations. There were 277 (70.66%) cases of NVE, 104 (26.53%) cases of PVE, and 11 (2.81%) cases of CDE. The majority of PVE occurred on prosthetic aortic valves (78/104, 75%), of which 72 (93.5%) were surgical aortic valve replacements (SAVR), 6 (7.8%) were transcatheter aortic valve implants, and one transcatheter pulmonary valve implant. Overall, underlying anatomy (p = 0.042) as well as the treatment approaches for IE (p < 0.001) were significantly associated with IE culprit microorganisms. Cross-reference between IE bacteraemia outcomes with the eHOMD was observed in 267/392 (68.11%) cases. Conclusions This study demonstrated that IE patients with a history of stroke, smoking, intravenous drug use, or dialysis were more likely to be infected with Staphylococcus aureus. CDE case participants and patients who had previous SAVR were most associated with Staphylococcus epidermidis. IE patients aged 78+ were more likely to develop enterococci IE than other age groups. Oral microorganisms indicated by the eHOMD are significantly observed in the IE population. Further research, through enhanced dental and medical collaboration, is required to correlate the presence of oral microbiota as causative factor for IE.